ANALYSIS OF THE RELIGIOUS COURT DECISION Number 119/Pdt.G/2020/PA.Plk REGARDING CHILDREN'S MADHIYAH SUPPORT FROM THE PERSPECTIVE OF HIFDZ NAFS AND JUDICIAL ACTIVISM THEORY - Alazlansyah, Muhammad; Nasution, Muhammad Sykri Albani (EKSEKUSI, 2025)
In the Palangkaraya Court Decision Number 119/Pdt.G/2020/PA.Plk there is a dynamic where the judge requires the ex-husband to provide child support as much as requested by the applicant without considering the income and financial strength of the ex-husband. So this study was conducted by analyzing the court's decision in the Theory of hifdz nafs in Maqashid Syariah and the theory of Judicial Activism. This study uses a qualitative method with a research location which is a Library study. The results of this study indicate that the Decision made by the judge at the Palangkaraya Religious Court is stated in the purpose of maintaining the soul which is implemented in the provision of food, drink, clothing and also Education. Meanwhile, the Judge's Decision is at the level of hajiyat (secondary) not dharuriy (primary). Therefore, in the theory of Judicial Activism, judges at the Palangkaraya Religious Court should reinterpret and formulate decisions that accommodate peace between two people who have separated, by applying the Interpretive Fidelity dimension to obtain substantive justice.Keywords: Livelihood, Hifdz Nafs, Judicial Activism.